Validation and field application of tailor-made nitrogen dioxide passive samplers - Bootdee S. (2014)
This study describes the validation and field application of new tailor-made passive samplers for nitrogen dioxide measurements. These samplers consist of polypropylene diffusion tubes containing glass fiber filters impregnated with 20 % triethanolamine. The tube was constructed from locally made material. The sampler is simple, lightweight, cheap, easy to use and suitable for simultaneous and multipoint measurements. Nitrogen dioxide concentrations obtained from the passive samplers were strongly correlated with chemiluminescence analyzer (r = 0.924). The nitrogen dioxide measurements by the passive samplers have been recorded at 20 sampling sites in Chiang Mai City, Thailand, once a month (3 days of exposure) from November 2007 to April 2008. The sampling sites were located across the city in alignment with the major wind direction. The highest nitrogen dioxide concentrations (28.1-45.1 ppbv) were found in the urban areas with high level of traffic density and human activity. Meteorological conditions, i.e., wind direction/speed and precipitation, were considered for their influence on nitrogen dioxide concentrations. Due to a calm wind occurring during the sampling, its direction had, therefore, no significant effect on nitrogen dioxide concentrations collected from the different locations. However, the mean nitrogen dioxide concentrations were higher at the downwind sites than at the upwind locations. Unlike wind, rain precipitation obviously affected pollutant concentration levels. In regard to the spatial and temporal variations of nitrogen dioxide concentrations in the study sites, it was deduced that their levels were much more affected by local activities, such as traffic density and biomass burning, rather than meteorological factors. © CEERS, IAU 2012.